PENGARUH INTERPERSONAL TRUST TERHADAP ONLINE SELF-DISCLOSURE PENGGUNA MEDIA SOSIAL INSTAGRAM PADA REMAJA AWAL - Yulitri, Sherly; Mardianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to determine the influence of interpersonal trust on online self-disclosure in early adolescent users of Instagram social media. This research uses a quantitative approach with causal methods and simple regression analysis. The subjects in this research were 270 early teenage Instagram users. The sampling technique uses a purposive sampling method. The instruments used in this research were the interpersonal trust scale and the online self-disclosure scale. The research results show that there is a positive and significant influence between interpersonal trust on online self-disclosure with a significance value of 0.000 (p < 0.05), so the hypothesis is accepted. The regression coefficient value of 0.197 shows that the higher the level of interpersonal trust, the higher the level of online self-disclosure among early teenage Instagram users. In addition, the coefficient of determination (R Square) value of 0.119 shows that interpersonal trust contributes 11.9% to online self-disclosure, while the remaining 88.1% is influenced by other factors outside the research.